Analysis of changes in the serum level nt-probnp after ace inhibitors therapy in patients with heart failure - Hartoto, Halla Hisan; Zulkarnain, Bambang Subakti; Aminuddin, Muhammad (Folia Medica Indonesiana, 2017)
BNP secreted by left ventricle as response to wall stress in patient with heart failure. Elevated concentration of NT-pro-BNP correlate with severity of heart failure across all stages of the condition and left ventricle ejection fraction in patient. Several clinical trials have demonstrated that neurohormonal modulation on the RAAS decreases NT-proBNP level and results in favorable outcomes. One of the drug used for blocked RAAS system is ACE inhibitor, decrease of NT-proBNP level show response to therapy include therapy with ACE inhibitors. To analize changes in the levels serum NT-proBNP levels after ace inhibitor therapy in patients with heart failure and monitoring creatinine serum. This study was a observational, prospective, non-randomized trial involving patient age 21-75 years, with NYHA class II-III HF, using ACE inhibitor therapy plus other therapy maximum 3 months before study without ARB or beta blocker. We compared serum NT-pro-BNP and creatinin serum parameters before and after two months treatment with ACE inhibitor. This study conducted in cardiovascular ambulatory patient dr. Soetomo hospital Surabaya. Between August-November 2015, 13 patient (38-63 years, 6 woman, 7 men) include in this study. The mean baseline level of NT-proBNP is 2166.92±1236.73 pg/ml, and creatinin serum 1.023±0.601 mg/dL. The NT-pro-BNP were significantly decreased after two months of treatment with ACE inhibitors 1508.23±651 pg/mL (p=0.025), there were no significant differences creatinin serum between two groups 0.951±0.0365 mg/dL (p=0.111). The results demonstrated the benefits of ACE inhibitor on the neurohormonal profile in patients with HF. If necessary we could measure NT-proBNP level to support prognosis data and monitoring effectivity therapy especially ACE inhibitor which had antiremodelling effect towards patients with HF.